Analgesic Efficacy of Pfannenstiel Incision Infiltration with Ropivacaine 7.5 mg/mL for Caesarean Section. (30th June 2010) - Nguyen, N. K.; Landais, A.; Barbaryan, A.; M'Barek, M. A.; Benbaghdad, Y.; McGee, K.; Lanba, P.
Abstract : Background . Pain after Caesarean delivery is partly related to Pfannenstiel incision, which can be infiltrated with local anaesthetic solutions. Methods . A double- blind randomized control trial was designed to assess the analgesic efficacy of 7.5 mg/mL ropivacaine solution compared to control group, in two groups of one hundred and forty four parturients for each group, who underwent Caesarean section under spinal anaesthesia: group R (ropivacaine group) and group C (control group). All parturients also received spinal sufentanil (2.5 μ g). Results . Ropivacaine infiltration in the Pfannenstiel incision for Caesarean delivery before wound closure leads to a reduction of 30% in the overall consumption of analgesics (348 550 mg for group R versus 504 426 mg for group C withP < .05 ), especially opioids in the first 24 hours, but also significantly increases the time interval until the first request for an analgesic (4 h 20 min± 2 h 26 for group R versus 2 h 42± 1 h 30 for group C). The P values for the two groups were:P < .0001 for paracetamol, P < .0001 for ketoprofen and P for nalbuphine which was the most significant. There is no significant difference in the threshold of VAS in the two series. Conclusion . This technique can contribute towards a programme of early rehabilitation in sectioned mothers, with earlier discharge from the post-labour suite.